2018
DOI: 10.1074/jbc.ra118.002350
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchyme homeobox 1 mediates transforming growth factor-β (TGF-β)–induced smooth muscle cell differentiation from mouse mesenchymal progenitors

Abstract: Differentiation of smooth muscle cells (SMCs) is critical for proper vasculogenesis and angiogenesis. However, the molecular mechanisms controlling SMC differentiation are not completely understood. During embryogenesis, the transcription factor mesenchyme homeobox 1 (Meox1) is expressed in the early developing somite, which is one of the origins of SMCs. In the present study, we identified Meox1 as a positive regulator of SMC differentiation. We found that transforming growth factor-β (TGF-β) induces Meox1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…More importantly, Meox1-induced SDF-1α in VSMC acts as a signpost to guide the directional migration of these cells into the intimal. These results are consistent with previous studies that found that Meox1 could induce MSC differentiation into VSMC [ 33 ]. In a word, the spatio-temporal model of Meox1 expression could trigger the engagement of Sca-1+ progenitor stem cells during the neointima formation.…”
Section: Discussionsupporting
confidence: 94%
“…More importantly, Meox1-induced SDF-1α in VSMC acts as a signpost to guide the directional migration of these cells into the intimal. These results are consistent with previous studies that found that Meox1 could induce MSC differentiation into VSMC [ 33 ]. In a word, the spatio-temporal model of Meox1 expression could trigger the engagement of Sca-1+ progenitor stem cells during the neointima formation.…”
Section: Discussionsupporting
confidence: 94%
“…PLSs were relatively stable across all time points (Figure 2B), expressed genes associated to cell migration and morphogenesis, known stromal cell markers Cd248 (Smith et al, 2015), Pi16 (Regn et al, 2016;Xie et al, 2018), and relatively higher levels of Ly6a, previously used as a marker to enrich for putative cardiac progenitor cells (Tang et al, 2018;Farbehi et al, 2019;Oh et al, 2003;Figures 2C-2E and S4C). LR fibroblasts were prevalent at d14-d28 (maturation phase), expressing a relatively higher level of genes associated with cell differentiation, osteogenesis, and regulation of matrix remodeling and deposition, including Adamtls2 and Cilp, secreted proteins involved in the negative regulation of TGF-b availability (Le Goff et al, 2008) and activity (Zhang et al, 2018), fibrillogen-esis (Koo et al, 2007), and fibrosis (van Nieuwenhoven et al, 2017;Zhang et al, 2018); Col8a1, an extracellular matrix (ECM) component conferring tensile strength that supports vessel integrity and structure (Kittelberger et al, 1990) upregulated in the presence of vascular injury (Gerth et al, 2007;Kittelberger et al, 1990;Lopes et al, 2013); and the transcription factor Meox1, which is involved in embryonic somitogenesis and TGF-b-induced differentiation of SMCs (Dong et al, 2018;Figures 2C-2E and S4C). Meox1 is also implicated in cardiac pathological hypertrophy (Lu et al, 2018) and is downregulated during in vitro phenoconversion from fibroblasts to Acta2 + Myofb (Cunnington et al, 2014).…”
Section: Dynamics Of Stromal Populations Involved In Scar Formationmentioning
confidence: 99%
“…Seurat analysis with 24 PC and resolution 0.5 was used to define 16 main clusters. the presence of vascular injury (Gerth et al, 2007;Kittelberger et al, 1990;Lopes et al, 2013); and the transcription factor Meox1, which is involved in embryonic somitogenesis and TGF-b-induced differentiation of SMCs (Dong et al, 2018;Figures 2C-2E and S4C). Meox1 is also implicated in cardiac pathological hypertrophy (Lu et al, 2018) and is downregulated during in vitro phenoconversion from fibroblasts to Acta2 + Myofb (Cunnington et al, 2014).…”
Section: Dynamics Of Stromal Populations Involved In Scar Formationmentioning
confidence: 99%